2023
DOI: 10.3390/pr11071960
|View full text |Cite
|
Sign up to set email alerts
|

Low-Carbon and Energy-Saving Path Optimization Scheduling of Material Distribution in Machining Shop Based on Business Compass Model

Yongmao Xiao,
Hao Zhang,
Ruping Wang

Abstract: In order to reduce carbon emission and energy consumption in the process of raw material distribution, the workshop material distribution management model was established based on the business compass model; it can help guide enterprises to manage workshop production. Based on the raw material distribution equipment, a path calculation model considering the carbon emission and energy consumption in the process of raw material distribution was established. The dung beetle optimizer was selected for the optimiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…It can be observed that dung beetles utilize the sun for navigation, with the arrow indicating the rolling direction [32]. Assuming that the intensity of the light source also influences the rolling path of dung beetles, the position of the roller beetle is updated and can be represented as follows [33]: Assuming that the intensity of the light source also influences the rolling path of dung beetles, the position of the roller beetle is updated and can be represented as follows [33]:…”
Section: Roller Beetlementioning
confidence: 99%
“…It can be observed that dung beetles utilize the sun for navigation, with the arrow indicating the rolling direction [32]. Assuming that the intensity of the light source also influences the rolling path of dung beetles, the position of the roller beetle is updated and can be represented as follows [33]: Assuming that the intensity of the light source also influences the rolling path of dung beetles, the position of the roller beetle is updated and can be represented as follows [33]:…”
Section: Roller Beetlementioning
confidence: 99%
“…Compared to the grey wolf algorithm, whale algorithm, and sparrow algorithm, DBO holds advantages such as robust optimization ability, rapid convergence, high solution accuracy, and robustness. Scholars have used these advantages to solve complex parameter optimization problems [22,23]. Consequently, DBO is utilized for optimizing VMD's parameters.…”
Section: Introductionmentioning
confidence: 99%